PEMBINAAN PERNIKAHAN MUALLAF DALAM RANGKA MEWUJUDKAN KELUARGA HARMONIS (Studi di Desa Sumber Arum, Kotabumi Lampung Utara) - Syaibani, Syaibani (Universitas Islam Negeri Raden Intan Lampung, 2018)
The problem in this article is how to guide Muslimconverts in Sumber Arum Village, Kotabumi, NorthLampung? Is it the impact of fostering a marriageconvert to family harmony in Sumber Arum Village,Kotabumi, North Lampung? This research is fieldresearch and the data obtained from interviews,observations, and documents. Data analysis was carriedout descriptively analytically. This study found that theimplementation of the Muslim convert marriage inSumber Arum village was basically in the category ofindependent marriage formation. The coaching processis usually carried out at a time and place agreed upontogether. The Guidance material includes IslamicAqeedah, Fiqh, Morals, Munakahat and Rights andObligations of husband / wife. The activity has apositive impact on three main things, namely: themaintenance of converts (hifzu ad-din), the maintenanceof families and descendants of converts (hifzu an-nasl),and the creation of harmonious families.